Impact of various storage conditions on enzymatic activity, biomass components and conversion to ethanol yields from sorghum biomass used as a bioenergy crop - Rigdon, Anne R.; Jumpponen, Ari M.; Vadlani, Praveen V.; Maier, Dirk E. (My University, 2013)
With increased mandates for biofuel production in the US, ethanol production from lignocellulosic substrates is burgeoning, highlighting the need for thorough examination of the biofuel production supply chain. This research focused on the impact storage has on biomass, particularly photoperiod‐sensitive sorghum biomass. Biomass quality parameters were monitored and included biomass components, cellulose, hemicellulose and lignin, along with extra‐cellular enzymatic activity (EEA) responsible for cellulose and hemicellulose degradation and conversion to ethanol yields. Analyses revealed dramatic decreases in uncovered treatments, specifically reduced dry matter content from 88% to 59.9%, cellulose content from 35.3% to 25%, hemicellulose content from 23.7% to 16.0% and ethanol production of 0.20 g Lˉ¹ to 0.02 g Lˉ¹ after 6 months storage along with almost double EEA activities. In contrast, biomass components, EEA and ethanol yields remained relatively stable in covered treatments, indicating covering of biomass during storage is essential for optimal substrate retention and ethanol yields.
Keywords: Lignocellulosic ethanol production; Ethanol; Biomass; Storage; Extra‐cellular enzyme activity; Biofuels; Composition